Why do firms default on their foreign currency loans? The case of Hungary. (September 2018) - Vonnák, Dzsamila
Highlights: Decomposition of default rates of foreign currency (FX) borrowers into currency and composition effects. Less creditworthy firms are self-selected to FX loans, currency shocks further weakened their loan performances. More creditworthy firms that were well-prepared for the currency risks also borrowed in FX. The institution of FX lending and the characteristics of borrowers have to be jointly examined. Abstract: I isolate the effect of the choice of foreign currency on the loan performance of firms borrowing in different currencies in crisis times. I use a novel micro-level dataset from Hungary to decompose the factors contributing to the worse loan performance of foreign currency borrowers compared to local currency debtors. I find that foreign currency denomination can worsen loan performance considerably, while selection also contributes significantly to the default differences. On the one hand, per se less creditworthy firms borrowed in foreign currency and during the crisis the foreign currency shocks further weakened their loan performances. On the other hand, more creditworthy firms that were also well-prepared for the currency risks also borrowed in foreign currency. My results suggest that not the institution of foreign currency lending per se that should be blamed for the bad loan performance of foreign currency borrowers, instead one should consider the characteristics of the borrowers.